1998
DOI: 10.2307/4003615
|View full text |Cite
|
Sign up to set email alerts
|

Seed Weight and Germination Time Affect Growth of 2 Shrubs

Abstract: The objective of this study was to investigate relationships between seed size, time of germination, and seedling growth in winterfat (Cerutoides lanata (Pursh) J. T. Howell) and silver sagebrush (Artenzisia cuna Pursh). Individual seeds of winterfat were placed into 6 weight classes ranging from 1.5-2.0 to Z-4.0 mg seed-l while silver sagebrush seeds were separated into 7 classes ranging from 0.53 to 0.83 mg seed-l. Seeds were incubated at U°C, seedlings with radicles < 3.0 mm were removed at 1, 2,3, 4-5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…This increase in resources can speed up seed germination because the radicle can break the seed coat faster, speeding up the nutrient absorption from the soil, and hence seedling growth [26][27][28]. This faster seedling establishment is an advantage for new stand establishment because earlier developing seedlings can obtain more resources, thereby gaining a competitive advantage to later germinating seeds [29,30]. We also found a significant difference in seed germination success and rate among our three sampling years.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This increase in resources can speed up seed germination because the radicle can break the seed coat faster, speeding up the nutrient absorption from the soil, and hence seedling growth [26][27][28]. This faster seedling establishment is an advantage for new stand establishment because earlier developing seedlings can obtain more resources, thereby gaining a competitive advantage to later germinating seeds [29,30]. We also found a significant difference in seed germination success and rate among our three sampling years.…”
Section: Discussionsupporting
confidence: 51%
“…L. chinensis, a perennial, rhizomatous grass widely distributed in the eastern regions of the Eurasian steppe zone [30]. L. chinensis is tolerant to saline-alkali soil, extreme drought and cold, and has high palatability for livestock likes cow and sheep [31].…”
Section: Species Descriptionmentioning
confidence: 99%
“…Booth and Morgan (1993) and Hou and Romo (1998a) indicated that seedlings developing from early-germinating diaspores might have greater survival because they produce more vigorous seedlings than late germinating ones. Late emerging seedlings of winterfat establish poorly under drought stress compared with seedlings emerging early (Waddington and Shoop 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In both 1995 and 1996, weight of seeds became significantly heavier for seeds collected later in the growing season (Table 2). Heavier seeds within a seed lot have been shown to exhibit higher germination amounts and better seedling emergence characteristics than lighter seeds (Aiken and Springer 1995, Limbach and Call 1996, Hou and Romo 1998. Seeds collected later in the process of seed head maturation also exhibit greater seed germination amounts (Phaneendranath et al 1978).…”
Section: Resultsmentioning
confidence: 99%